Our cups are full : pottery and society in the Aegean Bronze Age : papers presented to Jeremy B. Rutter on the occasion of his 65th birthday - Gauss, Walter, 1969-; Lindblom, Michael,; Smith, R. Angus K. 1968-; Wright, James C., 1946-; Rutter, Jeremy B., (Archaeopress, 2011)
This is a collection of papers presented to Jeremy Rutter to mark his 65th birthday.